MODERN ASPECTS OF PATHOGENESIS OF BRUCELLOSIS - Djabbarova N.R.; Kudratova Z.E.; Hamidova B.; Nurullayeva Ch. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
The pathogenesis of brucellosis in humans is determined by the characteristics of the pathogen, particularly the absence of classic virulence factors such as endotoxins or exotoxins, fimbriae, and the ability to suppress apoptosis. It is believed that S-LPS contributes to the blockade of innate immunity in the early stages of the infectious process and the bactericidal activity of the immune system. *Brucella* impedes the recognition by TLRs and complement, which also results in an inadequate antimicrobial effect of immunity in brucellosis [4,5,6].